Indigenous innovation - Waterloo Institute for Social Innovation and Resilience (Waterloo Institute for Social Innovation and Resilience, 2014)
Overview This research space can be described as an opportunity to explore trust, balance, respect, and understanding in intercultural relationships between indigenous and non-indigenous peoples in Canada, with an overall aim of fostering new, responsible, reciprocal and respectful relationships in place of old conflicts .Preliminary research suggests that social innovations
Keywords: Canada; Centre de recherche universitaire; Libre accès